Shoulder strength and range of motion in healthy collegiate softball players - Biaggi, K.; Farmer, B.; Hobson, M.; Self, C.; Grindstaff, T. L. (Journal of Athletic Training, 2021)
Context: Shoulder range of motion (ROM) and strength are key injury evaluation components for overhead athletes. Most normative values are derived from male baseball players, with limited information specific to female softball players. Objective: To determine between-limbs differences in shoulder ROM and strength in healthy collegiate softball players. Design: Descriptive laboratory study. Setting: University research laboratory and collegiate athletic training room. Patients or Other Participants: Twenty-three healthy collegiate softball players (age = 19.9 ± 1.2 years, height = 170.5 ± 4.3 cm, mass = 78.4 ± 11.3 kg). Main Outcome Measure(s): Shoulder ROM (internal rotation [IR] and external rotation [ER]), isometric strength (IR, ER, flexion, abduction [135°], and horizontal abduction), and a measure of dynamic strength (Upper Quarter Y-Balance Test) were obtained. Paired-samples t tests were used to determine between-limbs differences for each outcome measure. Results: Participants had more ER ROM (12° more) and less IR ROM (12° less) in the dominant arm, relative to the nondominant arm. No differences were present between limbs for any of the isometric strength measures or the Upper Quarter Y-Balance Test reach directions. Conclusions: Female collegiate softball players demonstrated typical changes in ER and IR ROM in the dominant arm and relatively symmetric performance across strength measures, which contrasts with previous findings in male baseball players.